A REVIEW: AZADIRACHTA INDICA AS ANTIHYPERLIPIDEMIC ACTIVITY - Baghel, Shalu; Singh, Charanjeet (Journal of Biomedical and Pharmaceutical Research, 2019)
Antihyperlipidemic agents having various pharmacological actions are being tested clinically3. Elevated lipid levels result from increased absorption through the gut or enhanced endogenous synthesis and therefore two ways are feasible to reduce hyperlipidemia; to block endogenous synthesis or to decrease absorption. Whole plant of Azadirachta indica gives the Antihyperlipidemic activity. Several genetic conditions are known to responsible for primary Hyperlipidemia, such as lipoprotein lipase deficiency, apolipoprotein C-II deficiency etc. In our study we choose cholesterol diet which contains the common ingredients in our daily food. Cholesterol feeding has been often used to elevate serum or tissue cholesterol levels to assess the hypercholesterolemia- related metabolic disturbances in animals. Cholesterol feeding alone however does not affect the serum TG level. Keywords: Azadirachta indica, antihyperlipidemic, antiatherosclerotic activities, Maceration.